Penerapan Fungsi Ekonomi dalam Supply Chain Management - Doktoralina, Caturida Meiwanto; Lestari, Lestari; Mareta, Sigit (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Understanding the application of zakat accounting principles in sharia economics in accordance with the provisions applicable in Indonesia is important for the younger generation. Consequently, it is imperative to comprehend the way the younger demographic engage with one another, to effectively address the incorporation of zakat empowerment. Community Service Activities (PkM) are carried out by first observing partners' initial difficulties, then the counseling method uses lecture techniques. It is hoped that through community involvement, the PkM initiative will enable young community groups to understand the importance of Zakat in the local economy and that BAZ/LAZ, local institutions, will be able to use it to help increase Zakat payments and distribute Zakat. more easily accessible, as an effort to improve the economy. Increasingly competitive market issues and rapid business changes throughout the world today require organizations to reconsider supply chain management (SCM) strategies because the same SCM strategy may not be suitable for all organizations. The success of a strategy in a particular business does not necessarily mean its success in other businesses. The result of this PkM Program is that participants form an attitude of understanding and realizing the role of Zakat accounting in supporting the economic function of SCM from an Islamic perspective.